1986
DOI: 10.1161/01.atv.6.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic heterogeneity of low density lipoproteins in primary hypertriglyceridemia.

Abstract: The kinetics of two subfractions of low density lipoproteins (LDL) were examined in nine patients with primary hypertriglyceridemia. LDL was subjected to equilibrium ultracentrifugation, and three patterns of LDL subfractions were noted. The LDL of five patients with moderate hypertriglyceridemia (plasma triglycerides (TG) ranging from 333 to 580 mg/dl) appeared to contain two distinct subfractions. One was less dense and had a high TG content; the other was more dense and had a reduced content of all lipids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Hypertriglyceridemia is usually associated with a shift of the LDL distribution from lighter to denser particles, and this pattern of elevated plasma triglyceride, a predominance of dense LDL, and low high-density lipoprotein cholesterol is proposed as a distinct form of dyslipidemia called the atherogenic lipoprotein phenotype. 18 Fisher et al, 19 Packard and colleagues, 20 and Vega et al 21 hypothesized from kinetic studies that dense LDL is formed from the substantial light VLDL production, heightened activity of cholesteryl ester transfer protein-mediated exchange of lipids between light VLDL and LDL, and finally the conversion of the triglyceride-enriched, cholesterol ester– depleted light LDL to dense LDL via the function of hepatic lipase. 22 They and others demonstrated a major flux pathway from light VLDL to dense LDL with little removal of intermediates, whereas in contrast, normotriglyceridemic subjects have much more direct LDL production and removal of dense VLDL and IDL.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia is usually associated with a shift of the LDL distribution from lighter to denser particles, and this pattern of elevated plasma triglyceride, a predominance of dense LDL, and low high-density lipoprotein cholesterol is proposed as a distinct form of dyslipidemia called the atherogenic lipoprotein phenotype. 18 Fisher et al, 19 Packard and colleagues, 20 and Vega et al 21 hypothesized from kinetic studies that dense LDL is formed from the substantial light VLDL production, heightened activity of cholesteryl ester transfer protein-mediated exchange of lipids between light VLDL and LDL, and finally the conversion of the triglyceride-enriched, cholesterol ester– depleted light LDL to dense LDL via the function of hepatic lipase. 22 They and others demonstrated a major flux pathway from light VLDL to dense LDL with little removal of intermediates, whereas in contrast, normotriglyceridemic subjects have much more direct LDL production and removal of dense VLDL and IDL.…”
Section: Discussionmentioning
confidence: 99%
“…The previous kinetic studies for total LDL have shown varying FCR and TR values in NIDDM [52][53][54], while those for dense LDL particles have not been studied previously in NIDDM. In most but not all non-diabetic hyperfipidaemic subjects the dense LDL fraction was cleared slower than the light fraction [55][56][57], while in almost all of our diabetic patients the dense LDL fraction was cleared faster than the light fraction. In contrast to earlier findings in familial hypercholesterolaemia [55], none of the radioactivity in the dense fraction was transferred to the light fraction in our diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have also demonstrated relationships between LDL particle size and triglyceride metabolism [142][143][144][145]. However, the association of LDL particle size with triglyceride levels in subjects with pattern B did not influence the LDL cholesterol or apo B responses to the low-fat diet [138).…”
Section: Journal Of the American College Of Nutrmonmentioning
confidence: 93%